(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article deals with the analysis of the approach to managing business processes based on the concept of system constraints theory. The actual tasks concerning the management of an employee’s intellectual resource in the context of operational management on the basis of the theory of system constraints are revealed. It was emphasized on the necessity of applying the methodology of TOC in order to manage the intellectual resources of a worker. The 5-step method of controlling worker restrictions on the basis of TOC is proposed. Formed proposals for the introduction of scientific research into the model of intellectual organization.